The Female Vs society in Sylvia Plath’s “The Bell Jar (Journal of the College of Basic Education, 2022)
In a biographical note by Lois Ames, Sylvia Plath says about her novel, The Bell Jar, “….I’ve tried to picture my world and the people in it as seen through the distorting lens of a bell jar.”1In thisautobiographical novel, the heroine is looking at people through this distorted lens. The novel describes the oppressive and patriarchal society in which the main character, Esther Greenwood, lives